The Governance Behind the Green: How CSR Strategy and Stakeholder Engagement Shape ESG Performance in Southeast Asia - Sally, Tham Tjin Shia Alias; Andrian, Tommy (International Journal of Energy Economics and Policy, 2025)
The purpose of this study is to analyze the effect of CSR strategy, sustainability committee, and corporate governance board committee on ESG Score in Southeast Asia, with stakeholder engagement as a moderating variable. The study uses quantitative methods using secondary data sourced from Refinitiv, with companies listed on stock exchanges in Indonesia, Malaysia, Thailand, Singapore, and the Philippines from 2014 to 2023. This study uses balanced panel data with a total of 1,350 observations processed using SPSS 30 statistical software. The results showed that CSR strategy and corporate governance board committee have a significant positive effect on ESG score, while sustainability committee does not have a significant effect. Stakeholder engagement weakened the relationship between CSR strategy, sustainability committee, and corporate governance board committee on ESG score. These findings highlight that the impact of CSR and governance strategies on sustainability is influenced by local institutional and cultural factors. ESG implementation in Southeast Asia should balance external pressures with strong internal commitment by embedding sustainability across all operations and reporting levels. Companies must ensure that CSR initiatives are measurable and transparent, strengthen sustainability and governance committees, and promote authentic stakeholder engagement through continuous dialogue and evidence-based sustainability reporting.